John P. McGovern, MD : A Lifetime of Stories - Boutwell, Bryant (Book collections on Project MUSE., 2014)
John P. McGovern held seventeen professorships, received twenty-nine honorary doctorates, and established the nation's largest privately owned allergy and immunology clinic. He authored 252 professional publications including twenty-six books in the medical sciences and humanities, and served as president or chief elected officer of fifteen professional societies in medicine. In addition, the McGovern Foundation has given millions of dollars to various local and national health charities, and many Houston landmarks bear the McGovern name, including the McGovern Lake and McGovern Children'